2017
DOI: 10.1097/jac.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Uses of the Electronic Health Record Among US Pediatricians

Abstract: Little is known about how existing electronic health records (EHRs) influence the practice of pediatric medicine. A total of 808 pediatricians participated in a survey about workflows using the EHR. The EHR was the most commonly used source of initial patient information. Seventy-two percent reported requiring between 2 and 10 minutes to complete an initial review of the EHR. Several moderately severe information barriers were reported regarding the display of information in the EHR. Pediatricians acquire info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Poor communication [34,40,47,48,70,78,120] Dysfunctional workflow [29,38,44,45,47,61,73,89,91,[112][113][114][115]141,148] Data and information Data quality and accuracy [40,48,78,91,122,137,145] Decreased accessibility [39,40,43,70,106,126] Care for patients Face-to-face or direct communication [43,45,84,137] Quality of care [20,28,34,38,81,82,94,106,116,126,137,…”
Section: Theme Category Sub-category Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Poor communication [34,40,47,48,70,78,120] Dysfunctional workflow [29,38,44,45,47,61,73,89,91,[112][113][114][115]141,148] Data and information Data quality and accuracy [40,48,78,91,122,137,145] Decreased accessibility [39,40,43,70,106,126] Care for patients Face-to-face or direct communication [43,45,84,137] Quality of care [20,28,34,38,81,82,94,106,116,126,137,…”
Section: Theme Category Sub-category Referencementioning
confidence: 99%
“…Providers perceived that retrieving and locating necessary information in EHRs was difficult [148] and took longer than expected, which also had a negative impact on their efficiency [34,40,45]. Clinicians expressed concerns and frustration regarding the slowness of systems [91,96,113] and the time-consuming nature of patient documentation using EHRs [23,34,38,40,43,44,58,145,154], with 81.8% of the respondents (physicians) in a survey agreeing that "to document on paper is faster than on the EHR" [39]. Another survey showed that 71% of the respondents (physicians) perceived an increase in time spent on patient documentation following the implementation of EHRs [17].…”
Section: Work For Healthcare Providers/staffmentioning
confidence: 99%
“…For example, several studies have highlighted the importance of implementing an NHIN (Carroll, 2007; Dobalian et al, 2012; Kuperman et al, 2010; Valle et al, 2016). In many countries, the implementation of the EHRs has been recognised as a priority among other HITs (Buntin et al, 2011; Doberne et al, 2017; Martinez-Costa et al, 2014; Weinfeld and Mishori, 2017), and in various studies, the importance of using personal health records has been emphasised (Kang et al, 2015; Luo et al, 2012; Toscos et al, 2016). The development of a national data centre (Ahlqvist et al, 2007; Weng et al, 2016), interactive standards for HIT (Chronaki et al, 2014; Mookencherry, 2012; Mccarthy, 2016), information sharing between health information systems at a national level (Alexander et al, 2016; Vest and Abramson, 2015; Zaidan et al, 2015), telehealth (Dinesen et al, 2016; Tuerk et al, 2010; Teot, 2014) and developing m-health (Berrouiguet et al, 2016; Goyal and Cafazzo, 2013; Sikka and Barash, 2012) were among the technologies that have been discussed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…EMR systems like Epic and Centricity have replaced paper-based records and are now the standard of care throughout the United States. [22][23][24] These EMRs can interface with a virtually unlimited number of specialized modules. The current study investigated a system (designed by Partners HealthCare) that was based on the MyChart module of Epic, which allows clinicians to schedule, administer, score, and store patient-reported outcome measures (PROMs) for tracking BH outcomes as required by Early Periodic Screening Diagnosis and Treatment, CBHI, or other programs.…”
Section: Introductionmentioning
confidence: 99%